The Effect of Environmental Social Governance, Market Capitalization, Dividend Payout Ratio, and Financial Performance on SRI KEHATI Stock Returns - Lia Anggraeni; Diniati, Bintis Ti'anatud; Herliana Febrianti; Muhammad Asrori (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Abstract Objective – This study aims to analyze the influence of Environmental Social Governance, market capitalization, and financial performance on stock returns of companies listed in the Sri Kehati Index for the period 2020–2024, both simultaneously and partially. Design / Methodology / Approach – The research method applied is a quantitative approach. The sample was selected using purposive sampling, and the study employed secondary data. Data analysis methods include descriptive statistical analysis, panel data regression testing, classical assumption testing, hypothesis testing, and the coefficient of determination test. Data analysis was conducted using Eviews 12. Findings – The results indicate that, simultaneously, Environmental Social Governance, market capitalization, Dividend Payout Ratio, and financial performance have a positive and significant effect on stock returns of companies listed in the Sri Kehati Index for the period 2020–2024. Partially, market capitalization has a positive and significant effect on stock returns of companies in the Sri Kehati Index for the same period. Meanwhile, Environmental Social Governance, Dividend Payout Ratio, and financial performance do not have a significant effect on stock returns when tested partially. Research limitation / implications – This study is limited to a sample of 10 companies in the Sri Kehati Index, a relatively short observation period, and restricted variables, thus not covering all factors that may affect stock returns. Practical implications – This research encourages investors to pay closer attention to market capitalization and sustainability aspects in making investment decisions in companies listed in the Sri Kehati Index. Furthermore, the findings can serve as a reference for company management to strengthen financial performance and consider sustainability practices to enhance attractiveness in the eyes of investors. Originality / Value – The originality of this research lies in the integration of Environmental Social Governance analysis with fundamental company indicators (market capitalization, Dividend Payout Ratio, and financial performance) within the context of companies listed in the Sri Kehati Index, using the most recent research period of 2020–2024. The capital market is a platform used for trading various types of securities such as stocks, bonds, and other financial instruments through licensed brokers. In its development, the capital market has shifted its orientation not only toward financial gains but also toward sustainable development aspects or the Sustainable Development Goals (SDGs) (Arifianti & Widianingsih, 2023). The SDGs represent global development goals established by the United Nations, consisting of 17 objectives. Indonesia is among the countries committed to implementing the SDGs, as stated in Presidential Regulation No. 59 of 2017 concerning the Implementation and Achievement of the Sustainable Development Goals. Based on SDGs Score data, Indonesia recorded a score of 68.44 in 2020. This figure increased to 68.95 in 2021, then rose to 69.24 in 2022, and further to 69.43 in 2023. However, in 2024, Indonesia’s SDGs score slightly declined to 68.70.